AN EPIDEMIOLOGICAL STUDY OF NON-FATAL ROAD TRAFFIC ACCIDENTS CASES IN ALLAHABAD REGION, INDIA (Indian Internet Journal of Forensic Medicine and Toxicology, 2007)
The present Study evaluates various epidemiological factors associated with non-fatal Road Traffic  Accidents (Rats) cases. A total of 100 non-fatal RTA cases admitted to orthopedic, surgery or emergency  departments of SRN hospital during June 2005 to May 2006 were included for the purpose of present study.  All victims were thoroughly interviewed and followed up-to 30 days where necessary.  In non-fatal Rats, M/F ratio was 9:1. Mean age of accident was 36.6 year with range 11-80 years. Maximum  26(26%) cases were in the age group 21-30 years. Mostly non-fatal Rats occurred in winter seasons  40(40%). MTW occupants 46(46%) were maximally injured road user in non-fatal Rats. The lower  socioeconomic class predominated the study 58(58%) cases. Majority of the victims belonged to rural  habitat. Majority of victims showed low level of education, 72 % victims were educated up-to 10th standard.  Maximum 30(30%) accidents took place in between 16.00-20.00 hrs. Majority of accidents occurred on  highways. Four wheeled heavy vehicles were responsible for 36(36%) cases of non-fatal Rats. In 52% cases  the site of primary impact of the responsible vehicle was side. Maximum 34(34%) victims of non-fatal Rats  had to stay in the hospital for 3-4 weeks. Carelessness was responsible for a maximum 40 (40%) cases of  non-fatal Rats followed by fatigue and sleepiness 38 (38%), while alcohol was responsible for 22 (22%)  cases.
Keywords: preventable risk factors; ranked third